2020
DOI: 10.17580/em.2020.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Seismic productivity of blasts: A case-study of the Khibiny Massif

Abstract: The authors study the property of production-scale blasts to induce seismic events classified as micro shocks, rock bursts and earthquakes caused by sudden slips along faults. The study area is the production performance zone of Apatit’s Kirovsk Branch. It is situated in the southeast of the Khibiny Massif on the Kola Peninsula and is subjected to continuous autonomous seismicity monitoring. The subject of the research is the production blasts and seismic events recorded by the seismic monitoring station of Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…This study continues the research of the authors in the field of time-space patterns of seismic activity in the regions of mineral mining. It is already demonstrated that the number of seismic events triggered by blasting (seismic productivity of blasts) obeys an exponential distribution [1]. It is also found that under conditions of the induced seismicity in the Khibiny Massif, the distances between the seismic events and induced bumps comply with a power-series distribution [2].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…This study continues the research of the authors in the field of time-space patterns of seismic activity in the regions of mineral mining. It is already demonstrated that the number of seismic events triggered by blasting (seismic productivity of blasts) obeys an exponential distribution [1]. It is also found that under conditions of the induced seismicity in the Khibiny Massif, the distances between the seismic events and induced bumps comply with a power-series distribution [2].…”
Section: Introductionmentioning
confidence: 94%
“…In our study, we consider a single hierarchy scale, and we assume that the events in the series are independent of each other, and in each series, the number of the blast-triggered events with the magnitudes M m t 2 to the earthquake-triggered events with M t M m -1.5 obey the Poisson distribution with an average Λ [25]. In this case, the probability that all triggered events k take place at a distance less than x from a trigger is F r (x) k , where F r (x) is distribution (1). Using the formula of total probability, we obtain a distribution of the maximal epicentral distance R max from a trigger blast to a most remote aftershock in a series:…”
Section: Model Of the Aftershock Domainmentioning
confidence: 99%
See 3 more Smart Citations